Original paperEfficacy and safety of image-guided interstitial single fraction high-dose-rate brachytherapy in the management of metastatic malignant melanoma - Bretschneider, Tina; Mohnike, Konrad; Hass, Peter; Seidensticker, Ricarda; Göppner, Daniela; Dudeck, Oliver; Streitparth, Florian; Ricke, Jens (Journal of Contemporary Brachytherapy, 2015)
Purpose : Computed tomography (CT) or magnetic resonance imaging (MRI) guided brachytherapy provides high tumor control rates in hepatocellular carcinoma (HCC) and colorectal liver metastases. In contrast to thermal ablation methods such as radiofrequency ablation (RFA), much less restrictions apply with respect to tumor location or size. In this study, we determined the efficacy and safety of CT- or MRI-guided brachytherapy in metastatic melanoma. Material and methods : Fifty-two metastases of malignant melanoma in 14 patients were included in this retrospective study. Local tumor control and safety were evaluated as primary and secondary endpoints. Furthermore, we evaluated overall survival and progression free survival. Tumor locations were liver (n = 31), lung (n = 15), adrenal (n = 3), lymph nodes (n = 2), and kidney (n = 1). Treatment planning was performed using three-dimensional CT or MRI data acquired after percutaneous applicator positioning under CT or open MRI guidance. Subsequently, single fraction high-dose-rate (HDR) brachytherapy was applied using a 192Iridium source. Clinical and cross-sectional follow-up were performed every 3 months post intervention. Results : The median diameter of treated lesions was 1.5 cm (range: 0.7-10 cm). Doses between 15 and 20 Gy were applied (median dose: 19.9 Gy). The mean irradiation time ranged between 7-45 minutes. After treatment, there was one patient with a cholangitis. After a median follow up of five months, the median local tumor control was 90%. The median overall survival of the patients was 8 months. The median progression free survival of the patients was 6 months. Conclusion : Image-guided HDR brachytherapy is a safe and effective treatment procedure in metastatic malignant melanoma.